PEMBELAJARAN RANDAI MENGGUNAKAN METODE KOOPERATIF DI SMA NEGERI 1 BATUSANGKAR - Nesya Amalyah; Jagar L. Toruan; Marzam Marzam (FBS Universitas Negeri Padang, 2016)
This article to describe Randai using methods Cooperative learning in class X IPS 3 SMA Negeri 1 Batusangkar. Randai learning is one of the lessons in the school of art and culture that can be used by various methods, one of which with methods Cooperative.This type of research is qualitative descriptive method. The object of this research is the students of class X IPS 3 SMA Negeri 1 Batusangkar conducting Randai learning to study for 4 meetings. The research instrument is the researchers themselves assisted by other supporting facilities such as a camera. Based on the results of this research is that learning Cooperative Randai method in class X IPS 3 SMA Negeri 1 Batusangkar can increase students' activity during the learning process, then can improve student learning outcomes it is seen from the prior use of cooperative methods only 14 or 42.42% of students which reached a value above KKM after using the methods of cooperative learning outcomes of students increased to 27 or 81.81% of the students scored above the KKM as well as with the appearance or performance randai students. The impact of the application of cooperative methods to the students is that students are more motivated, responsive, and a pleasure to follow the lessons.